Dyspepsia: alarm symptoms, investigation and management. Issue 7 (18th April 2013) - Fong, Steven; Dunn, Jason
Abstract: Dyspepsia is a common symptom and the priority is to identify alarm signals that necessitate endoscopy referral. Our Drug review discusses its investigation, management and some new drug developments, followed by sources of further information.